Hereditary thrombophilia parameters in children with autism spectrum disorder and their mothers - Ray, Perihan Cam; Doğan, Merve; Bozdoğan, Sevcan; Gül, Gonca; Binokay, Hülya (Frontiers in Pediatrics, 2025)
ObjectiveAutism Spectrum Disorder (ASD) is a complex neurodevelopmental condition influencyed by genetic and environmental factors. There is emerging evidence of an association between hereditary thrombophilia and ASD, potentially mediated by impaired placental perfusion and resultant neuroinflammatory processes. This study aimed to investigate the frequency of thrombophilia-related genetic polymorphisms in children diagnosed with ASD and their mothers.MethodsA total of 24 children with ASD aged 2-6 and their mothers were compared with 24 age-matched healthy children and their mothers. Sociodemographic, developmental and genetic data were collected. A psychiatric evaluation was performed according to the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5), and the children were assessed using the Autism Behavior Checklist (ABC), the Modified Checklist for Autism in Toddlers (M-CHAT) and the Ankara Developmental Screening Inventory (ADSI). Thrombophilia-related polymorphisms, including FVL G1691A, FII G20210A, C677T MTHFR and 1298AC MTHFR, FXIII-Val34Leu and PAI-1 4G/5G, were analyzed using PCR-based methods. Statistical comparisons and logistic regression analyses were performed to evaluate associations with ASD.ResultsThe FXIII-Val34Leu heterozygous variant was significantly more prevalent in children with ASD (37.5% vs. 8.3%, p = 0.036) and their mothers (54.2% vs. 16.7%, p = 0.015) than in the control group. Logistic regression analysis revealed that the presence of the FXIII-Val34Leu heterozygous polymorphism in either the mother or child was associated with an approximately 4.130-fold increase in the odds of ASD (adjusted odds ratio = 4.130, 95% confidence interval = 1.180–5.300, p = 0.027). Other thrombophilia polymorphisms did not differ significantly between groups. Additionally, children with ASD exhibited significant delays in speech development and lower developmental scores across several domains.ConclusionThis study is among the first to examine the FXIII Val34Leu mutation in children with ASD and their mothers. Further large-scale, longitudinal studies are needed to investigate thrombophilia markers in relation to ASD.